Hydraulics and Mechanics of River Ice Jams - Uzuner,Mehmet Secil; Kennedy,John F. (1974)
An analytical model is developed for evolution of embacles in rivers. The differential equations underlying the analysis are the static force equilibrium relation for the fragmented ice cover; the unsteady, nonuniform momentum relation for the liquid flow beneath the ice; and the unsteady continuity equations for the solid and liquid phases. The analysis is limited to the case of uniform, rectangular channels. It yields predictions for the streamwise distribution of the thickness of the ice cover and the depth of flow beneath it; the flow depth and cover thickness over the uniform downstream reach where the jam thickness and flow depth are constant; the flow depth at the upstream end of the jam; and the velocity of propagation of the jam front. Estimates are also obtained for the rate of growth of a jam during early stages of its evolution, just following initiation.